ETHICS IN HUMAN RESOURCE MANAGEMENT: A CONCEPTUAL AND THEORETICAL ANALYSISA - OLANIPEKUN, Lateef Okikiola; JAYEOBA, Foluso Ilesanmi Phd (American Journals, 2022)
Most debates centered on HRM ethics have mainly concentrated on social and ecological responsibility of organisations; also, in recent years ethics has increasingly become an internal concern for organisations. In the past years, management has ignored employees’ interests as they prioritised the interests of shareholders. Human resource has become a very important resource to many organizations. This calls for the need to ensure justice and fairness in the manner in which this resource is handled. Employers in a typical organisation are in an increasingly advantaged position, whereby they dominate and govern the relationship between their employees and themselves. This shows the need for evaluating the role of the management in promoting morality and ethical procedures in dealing with employees, hence, this paper.